The Importance of the International Accounting Differences and Standards in the Theory and Practice - Romic, Lidija (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
We'll look at why accounting and financial reporting systems developed differently in different countries in this study. Finally, we'll look at research methodologies that attempt to explain disparities in accounting quality observed between nations using national factors, even after these countries transitioned to mandatory compliance with IFRS for listed companies. The indicated boundaries are determined by national or international standard setters, such as the IASB, who promulgate the techniques of recognition and measurement, consolidation presentation, and disclosure that the corporation must follow. When it comes to those concerns, certain standard setters give you a lot of options. Companies located in countries where standard setters allow many choices with regard to recognition and measurement issues have much more accounting flexibility in the presentation and valuation of this assets, liabilities, earnings and financial position. As a result, users of financial statements from companies in countries with greater accounting freedom will have more difficulty comparing the performance of different companies than users of yearly accounts from companies in countries with less accounting flexibility. Harmonization improves the comparability of financial data and provides greater openness to financial data users. As a result, there is less information asymmetry between stakeholders and businesses. Accounting provides an account – an explanation or report in financial terms – about the transactions of an organization. Accounting enables managers to satisfy the stakeholders in the organization (owners, government, financiers, suppliers, customers, employees etc.) that they have acted in the best interest of the stakeholders rather than themselves. This explanations are provided to stakeholders through financial statements or reports, often referred to as the company’s accounts’. The main financial reports are the Profit and Loss account, The Balance Sheet and the Cash flow statement. The presentation of financial reports must comply with Schedule 4 to the Companies Act, 1985, which prescribes the form and content of accounts. Section 226 of the Act requires the financial reports to represent a ‘true and fair view’ of the state of affairs of the company and its profits. The companies Act requires directors to state whether the accounts have been prepared in accordance with accounting standards and to explain any significant departures from those standards. For companies listed on the Stock Exchange, there are additional rules contained in the Listing Requirements, commonly known as the Yellow Book, which requires the disclosure of additional information.